Suture Repair of Full Radial Posterior Lateral Meniscus Tears Using a Central Midline Portal - Ouanezar, Hervé (Arthrosc Tech, 2017)
Full radial posterior lateral meniscus root tears are frequently associated with injuries to the anterior cruciate ligament. Left unrepaired, they result in loss of the meniscus hoop stress function and can lead to overload of the lateral compartment and early degenerative changes. Arthroscopic suture repairs show successful results with long-term follow-up. However, previously described suture repair techniques have often required special instrumentation and can be technically demanding. This Technical Note describes the use of an accessory portal through the patellar tendon as a safe and easy method for repairing full posterior radial tears of the lateral meniscus.